2013
DOI: 10.1063/1.4790876
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between structural parameters and the magnetocaloric effect in epitaxial La0.8Ca0.2MnO3/LaAlO3 thin film

Abstract: Dou, S. X. (2013). Correlation between structural parameters and the magnetocaloric effect in epitaxial La0.8Ca0.2MnO3/LaAlO3 thin film. Journal of Applied Physics, 113 (6), 063508-1-063508-6. Correlation between structural parameters and the magnetocaloric effect in epitaxial La0.8Ca0.2MnO3/LaAlO3 thin film Abstract An epitaxial La0.8Ca0.2MnO3/LaAlO 3 (LCMO/LAO) thin film was fabricated using the pulsed laser deposition technique to evaluate the correlation between the crystal structure and the magnetocalo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 48 publications
(49 reference statements)
1
4
0
Order By: Relevance
“…Bibes et al [17] studied the effect of the film thickness on the T C of the LCMO films grown by rf sputtering on STO substrates and found that T C increases from 100 K to 250 K by increasing the film thickness from 10 nm to 100 nm. Debnath et al [18] reported almost the same values of T C in comparison to our LCMO films for a 200 nm thick La 0.8 Ca 0.2 MnO 3 thin film grown by PLD process on LAO substrate. The 60 nm thick film, which is more relaxed compared to the 40 nm thick film, but do not reach that one of the bulk material (T C,bulk ¼ 270 K) [8].…”
Section: Magnetic Propertiessupporting
confidence: 79%
“…Bibes et al [17] studied the effect of the film thickness on the T C of the LCMO films grown by rf sputtering on STO substrates and found that T C increases from 100 K to 250 K by increasing the film thickness from 10 nm to 100 nm. Debnath et al [18] reported almost the same values of T C in comparison to our LCMO films for a 200 nm thick La 0.8 Ca 0.2 MnO 3 thin film grown by PLD process on LAO substrate. The 60 nm thick film, which is more relaxed compared to the 40 nm thick film, but do not reach that one of the bulk material (T C,bulk ¼ 270 K) [8].…”
Section: Magnetic Propertiessupporting
confidence: 79%
“…The entropy change in epitaxial 200 nm thick films of La 0.8 Ca 0.2 MnO 3 on LaAlO 3 substrate and La 0.7 Sr 0.3 MnO 3 / SrRuO 3 superlattices is of the same value or even exceeds ΔS observed in bulk counterparts (Zhang et al 2011, Debnath et al 2013. The observed ΔS in epitaxial films exhibits an anisotropy with the values of about 36 kJ m −3 K −1 in the ab plane and 25 kJ m −3 K −1 along the c-axis for a field change of 1 T. Debnath et al (2013) attributed the anisotropy in the MCE to a stronger exchange interaction in the manganite intralayer compared to that in the interlayer, forcing the magnetic moments to lie in the ab plane.…”
Section: Magnetocaloric Effect In Films and Multilayersmentioning
confidence: 74%
“…Otherwise, from [40] one can estimate the RCP of Ni-Co-Mn-In to 135 J kg −1 for μ 0 H = 1.9 T which is similar to the our results for μ 0 H = 2 T. For comparison, Gd shows RCP = 660 J kg −1 for μ 0 H = 5 T (estimated from [33]). Also, the RCP of Ni-Co-Mn-Al is comparable to other promising thin film systems like FeRh [41], MnAs [42], or La 0.8 Ca 0.2 MnO 3 [43], but in contrast to those only consists of common, inexpensive elements.…”
Section: B Magnetic and Magnetocaloric Propertiesmentioning
confidence: 76%